2000
DOI: 10.1016/s0014-5793(00)01273-4
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor‐like effects of placental alkaline phosphatase in human fetus and mouse embryo fibroblasts

Abstract: Human placental alkaline phosphatase (PALP) is synthesized in the placenta during pregnancy and is also expressed in many cancer patients; however, its physiological role is unknown. Here we show that in human fetus fibroblasts as well as normal and H-ras-transformed mouse embryo fibroblasts PALP stimulates DNA synthesis and cell proliferation in synergism with insulin, zinc and calcium. The mitogenic effects of PALP are associated with the activation of c-Raf-1, p42/p44 mitogen-activated protein kinases, p70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…This loop interacts with and may be stabilized by the putative calcium ion. It could therefore be responsible for the synergism observed between calcium and PLAP activity by intervening in substrate binding (15). In summary, the organization of the extended active site would be consistent with PLAP interacting with a large substrate.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…This loop interacts with and may be stabilized by the putative calcium ion. It could therefore be responsible for the synergism observed between calcium and PLAP activity by intervening in substrate binding (15). In summary, the organization of the extended active site would be consistent with PLAP interacting with a large substrate.…”
Section: Resultsmentioning
confidence: 81%
“…In NSAP, this specificity involves binding to collagen (11,12). In PLAP, evidence has accumulated over the past few years suggesting a role in cell division in both normal and transformed cells (13)(14)(15)(16). This role probably occurs through its phosphatase activity against phosphorylated proteins (14,17).…”
mentioning
confidence: 99%
“…Our study also shows that there is a good positive correlation between PLAP and blood pressure. Alkaline phosphatase is a ubiquitous enzyme involved in the transport of sugar and phosphate across the trophoblast cell membranes [22]. In normal pregnancy, the serum level of Total ALP is raised, attributable to the placental isoenzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased serum PLAP in pregnant women could be associated with intrauterine growth retardation (IUGR), premature rupture of membranes and premature labour [25]. It has been observed that in human fetal fibroblasts, PLAP stimulates DNA synthesis and cell proliferation in synergism with insulin, Zinc and Calcium, thus playing an important role in promoting fetal development [22].…”
Section: Discussionmentioning
confidence: 99%
“…The cells were treated for the indicated times with different concentrations of resveratrol, its derivatives or their vehicle, DMSO (o0.1%), which was used as a negative control. The relative changes in the number of viable cells were determined by the MTT assay as described previously (She et al, 2000), and a Labsystem Multiskan MS microplate reader was used to read the absorbance of formazan at a wavelength of 540 nm (She et al, 2000).…”
Section: Cell Proliferation Assaymentioning
confidence: 99%